A Comparison between Analytical and Numerical Solution of the Krogh’s Tissue Cylinder Model for Human Bone Marrow - Islam, MA (Journal of Chemical Engineering, 2010)
The Danish physiologist, August Krogh is the founder of the theory of oxygen transport to tissues. It was his famous tissue cylinder model developed for skeletal muscle, together with his colleague mathematician Erlang that laid down the foundation of the mathematical modeling of oxygen transport to tissues. Here an analytical solution of the Krogh’s model has been presented based on justifiable assumptions in order to validate the numerical approach used to solve more realistic oxygen transport models. The numerical solution of Krogh’s model is performed using computational fluid dynamics (CFD) software CFX 4.4. From the analytical solution, it is demonstrated that variation from the numerical result is less than 0.2% which in turn justifies the use of computer software in developing mathematical model for such physiological systems like BM. Journal of Chemical Engineering Vol.ChE 24 2006 1-6